Desenvolvimento e caracterização de biofilme à base de pectina, amido e sorbitol - Souza, Patrycia de (2021)
Aiming to reduce the use of packaging from non-biodegradable polymers, and the agro-industrial reuse and reduction of environmental contamination against plastics discarded in the environment, biofilms and biodegradable films obtained from agro-industrial waste have been studied as food packaging. Thus, this work aims to develop a biodegradable film based on pectin, starch and sorbitol, aiming to improve the properties of the film. For the manufacture of biofilms, commercial pectin with a degree of esterification of 46%, cassava starch and as a plasticizing agent (sorbitol) were used as raw material. The percentages varied from 25 to 75% for both polymers, keeping the amount of sorbitol constant. The films were produced by the casting method and showed good characteristics, malleability and homogeneity. The characterization of the films was carried out using the techniques of thermogravimetric analysis, x-ray diffraction, mechanical analysis, water vapor transmission, opacity, thickness and solubility test, and it was possible to observe that there was greater deformation with increasing starch percentage, in addition to the interaction between polymers with greater thermal stability for the film with greater addition of starch. After the production of the films using commercial pectin, the extraction of the pectin from the orange pomace was carried out. The extraction yielded 12 and 10%, and esterification degrees of 40% and 43% for pectins extracted from albedo and albedo and flavedo, respectively. The films obtained from commercial pectin still presented high solubility (100%), showing better response to the 25% starch and 75% pectin film (P25A75), with the lowest water vapor permeability rate, being the most suitable for coating fruits and vegetables. With the addition of starch and sorbitol to the pectin, the films became more malleable, with lower opacity and with better visual and tactile characteristics, indicating that the best film was in the percentages of 25% starch and 75% pectin (P25A75). The FTIR bands were similar for both extractions, it was possible to calculate the degree of esterification of the pectins obtained, for this, the bands at 1747 cm-1 and 1641 cm-1, referring to the C=O and COO groups -. The films obtained are promising for use in foods such as fruits and vegetables.